Malignant Pediatric Gliosarcoma Defies General Survival Data - Jovita Martin; Premkumar Devadoss; Kalaichelvi Kannan; Suresh Kumar Sundarraj (Case Reports in Medicine)
Gliosarcoma, a variant of glioblastoma multiforme, is a dimorphic tumor known for its intra-axial occurrence and poor survival of less than a year. Here is an 11-year-old boy with gliosarcoma. He had a near total excision and postoperative chemoradiotherapy. He has lived through the disease for over 34 months with a residual disease.This case report is to report an unusual long survival of gliosarcoma in a teenager (Ravisankar et al., 2012).